The agreement did not. 189 oit, as part of Costa Rican social legislation - Briones Briones, Eric (2017)
Ratification of international instruments corresponds to the first power of the Republic so that they may take effect within the Costa Rican legal system (theory of monism), as the Constitution of the country stipulates, specifically under Article Seven, that any international instruments such as public treaties, international agreements and concordats, duly approved by the Legislature, will take precedence over laws on the date of their enactment or on any other date specified therein. In this sense, by Law No. 9169 dated October 22, 2013, ILO Convention 189 on Decent Work for Domestic Workers was passed. This will certainly promote a rigorous development -within the occupational profile of domestic workers—of decent work, this being understood as a positive component of social justice, consistent with the reasonable expectations of every worker of performing productive, fairly remunerated labor in conditions of freedom, equality, equity and security (Brú Bautista). Lastly, this paper portrays a descriptive and reflective study with the aim of helping the legal practitioner to apply it, by approaching three main elements: Issues prior to the fair reform (Law No. 8726), constitutionality background, and international commitments as of such adoption. It finally presents the author’s appropriate considerations.